Standard specification for gray iron castings. (American Society of Testing Materials, 2008)
This specification covers gray iron castings intended for general engineering use where tensile strength is a major consideration. Castings are classified on the basis of the tensile strength of the iron in separately cast test bars. The surface of the casting shall be free of adhering sand, scale, cracks, and hot tears, as determined by visual examination. The test bars are designated into S, A, B, and C categories, according to the thickness of its controlling wall section. The casting shall be subjected to a tension test to determine its tensile strength. This abstract is a brief summary of the referenced standard. It is informational only and not an official part of the standard; the full text of the standard itself must be referred to for its use and application. ASTM does not give any warranty express or implied or make any representation that the contents of this abstract are accurate, complete or up to date.